Analisis Risiko Postur Kerja Pada Pekerjaan AngkatangkutDengan Metode Ovako Working Analysis System (OWAS) Terhadap Risiko Keluhan Muskuloskeletal Kuli Panggul Di Pasar Bunder Sragen - Ellyana, Ria Nur; , Tarwaka, PGDip Sc, M.Erg; , Dr. Suwaji, M.Kes (2014)
At work in manual activities, workers are required to have the physical ability (especially muscle and bone) to be produce something as desired. But it is necessary to know that that humans have physical limitations that have a tendency to experience problems associated with muscle and bone. The disorder is called with musculoskeletal complaints. The purpose of this study was to determine whether there is a relationship of risk postures on lift-transport job with the risk of musculoskeletal complaints in Bunder Market porters Sragen. This study is an observational cross sectional analytic approach. The samples in this study were 44 workers porters. Statistical tests using Pearson Product Moment Correlation with significance level (α = 0.05). Results of univariate analysis obtained by 38 people (86.4%) risk of musculoskeletal complaints have low risk levels and 6 (13.6%) complaints moderate risk level. While the results of the bivariate analysis of working posture on musculoskeletal complaints obtained value (pvalue = 0.040), so Ha accepted, where as if it seen from the correlation coefficient (r) of 0.312, have a low level of closeness relationship. So it can be concluded that there is a relationship between risk postures with complaints musculoskeleletal risk with a low level of closeness relationship . Suggested for porters workers to perform work and rest arrangements are balanced with adequate rest set pattern, so that the body still feels fit or fit while working.